GESTATIONAL DIABETES MELLITUS AND THE IMPLICATIONS FOR THE NURSING CARE IN THE PRENATAL PERIOD - Joice Moreira Schmalfuss; Lisie Alende Prates; Melissa de Azevedo; Vânia Schneider (Universidade Federal do Paraná, 2014)
This integrative literature review aims to identify the nursing care provided to women with gestational diabetes mellitus during the prenatal care, evidenced in the scientific literature, between 2004 and 2013. Data collection was undertaken in the LILACS AND BDENF databases, using the descriptors "gestational diabetes", "prenatal care", and "nursing". Seven publications were selected. Evidence was found for the existence of gaps in the care given to women with gestational diabetes, and the importance of the role performed by the nurse in the context of care for the pregnant woman, promoting the practice of self-care. The restricted number of publications on this issue points to the need for investment in production focusing on this population segment.